Development and application of an enhanced ART-Based neural network - Keem, Siah Yap; Chee, Peng Lim; W.M Lee, Eric; Junita, Mohamed Saleh (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.